Moving beyond Categorical Gender in Studies of Risk Aversion and Anxiety. Issue 4 (December 2019) - Wängnerud, Lena; Solevid, Maria; Djerf-Pierre, Monika
Abstract : Concepts such as risk aversion and anxiety have received renewed attention in various strands of gender and politics research. Most contemporary scholars suggest that gender gaps in this area are related to social norms and stem from social learning rather than from inherent gender traits. Very few, however, elaborate on the gender variable to reach a fuller understanding of the dynamics at work. In this study, we examined gender gaps in levels of anxiety, an area closely related to risk aversion, and we applied a combination of categorical measures of gender distinguishing between "woman, "man, " and "other" and scales capturing grades of femininity and masculinity in individuals. We label this approach fuzzy gender, and we suggest that it can be used to advance research in our field. The key finding is an interaction effect between categorical measures of gender and fuzzy gender: The more female characteristics in women, the higher the levels of anxiety. Moreover, there is no difference in levels of anxiety between men and women with few female characteristics. The data used draw from a large-scale survey among Swedish citizens in 2013.